Pre-hospital environment bleeding: from history to future prospects - Pereira, Bruno; Dorigatti, Alcir; Calderon, Luis; Negrão, Mayara; Meirelles, Guilherme; Duchesne, Juan (Anestezjologia Intensywna Terapia, 2019)
While the blood was related to life since antiquity, scientific investigations on anatomy and physiology of the circulation system had to wait until the arrival of the 16th century. In trauma patients, hemorrhagic shock is the main risk factor for multiple organ dysfunction and consequent increased mortality. On the pre-hospital setting intravenous administration of crystalloid solution became the more common intervention during resuscitation of trauma patient due to many reasons although currently new discussions have blossomed on regards type of fluids and resuscitation. The object of this manuscript is to review the history of pre-hospital care bleeding management and to gather new perspectives for the future. Herein authors discuss several issues on bleeding control: 1. Current status and future possibilities on stop the bleeding in the the pre-hospital setting – movements after the Hartford Consensus, use of topic homeostatic agents, tourniquets, REBOA and other radical interventions; 2. Damage control resuscitation in the pre-hospital environment – is massive transfusion protocol feasible at this setting? Tranexemic acid should be done? Possibilities that may improve survival and coagulopathy understanding; 3. Critical decision and decision making on stop the bleed; 4. Proposed flowchart on bleeding control. The implementation of measures to stop acute bleeding in the pre-hospital setting is a well-known and well-founded measure. However, the provision of current evidence demonstrates that these measures go far beyond compression and elevation of the limb as was known in the past. The deep understanding of the mechanism of coagulopathy and the new adjuvant arsenal to control bleeding are essential for a better quality of pre-hospital medical care as well as lower mortality rates.